Study on Dynamics Characteristic of High Speed Herringbone Gear Transmission System - Yongchao Yuan; Ziling Wang; Zhongming Liu; Jizhe Mao; Haiming Gang (Jixie chuandong)
Based on the finite element numerical analysis method， the dynamics equation of herringbone gear transmission system is given and the model of rotor-bearing-gear dynamics system is established. The influence of shear， bending， torsion， axial force， gyroscopic effect and internal damping of rotor shaft are considered in the modeling process， and the influence of time-varying mesh stiffness and transmission error of herringbone gear pair is also considered. The dynamics analysis of high speed gear rotor is also carried out， which is basically consistent with the measured data of the test gearbox.